Novel radiation-resistant optical fiber
By adopting the interface viscosity matching design of chlorine-doped fiber core and fluorine-doped cladding in the optical fiber, the problem of signal attenuation of the optical fiber in the radiation environment is solved, and higher radiation resistance and stability are achieved.
Patent Information
- Application Number
- CN202421026309.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-13
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2034-05-13
AI Technical Summary
Existing optical fibers are prone to form color centers in radiation environments, resulting in increased signal attenuation and radiation loss. The mismatch between the high-temperature viscosity of the fiber core and the cladding leads to interface unevenness, further enhancing radiation loss.
The interface viscosity matching design of chlorine-doped fiber core and fluorine-doped cladding is adopted to reduce radiation loss by forming a difference in refractive index between the core and cladding, and chlorine- and fluorine-doped at high temperatures to optimize the glass structure. Reduce interface irregularity.
It significantly reduces the radiation loss of the optical fiber, improves radiation resistance, and enables the optical fiber to transmit signals more stably in a radiation environment.
Smart Images

Figure CN222189509U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the field of optical fibers, in particular to a novel radiation-resistant optical fiber. Background Art
[0002] With the continuous development of modern communication technology, the applications where optical fiber may encounter nuclear radiation include not only tactical or strategic military systems, but also monitoring of nuclear waste and underground nuclear tests, visual observation of thermal reactor equipment, spacecraft communications, dosimetry and medical radiation, etc. The key to breaking through the technical barriers of nuclear power optical cable products lies in improving the radiation resistance, flame retardancy, operating temperature and service life of optical fiber cables.
[0003] Radiation-resistant optical fiber can be used in technical fields such as spacecraft, aerospace vehicles, deep space exploration, and ground nuclear facility monitoring. At the same time, after improvement, the product can be promoted and applied in nuclear power plants, nuclear submarines, nuclear aircraft carriers, airborne optical fiber wiring, satellite antenna remote microwave optical fiber lines, satellite communication pulse forwarding, communication satellite phased array antennas, and launch vehicles, and has a very broad application prospect.
[0004] Radiation is divided into two categories: ionizing radiation and non-ionizing radiation. Alpha rays, beta rays, gamma rays, X-rays, protons and neutrons are ionizing radiation, while infrared rays, ultraviolet rays, microwaves and lasers are non-ionizing radiation. Ionizing radiation is usually referred to as radiation or radiation exposure. Radioactive isotopes release three types of radiation when they decay: alpha rays, beta rays and gamma rays. In addition, there is neutron radiation, which is not produced by decay, but mainly by nuclear reactions.
[0005] When radiation-resistant optical fiber is irradiated by high-energy rays (such as electron beams, neutron beams, gamma rays, X-rays, and ultraviolet lasers), electrons in the atomic shells in the quartz optical fiber will be ionized to produce electron-hole pairs and displacement of the atomic nucleus and structural changes. When electrons or holes are captured by the inherent defect structure in the quartz glass network, they may be transformed into other types of point defect structures, forming new absorption centers in the glass material, which are commonly known as color centers. Color centers are divided into electron capture centers and hole capture centers. The forms of color centers are: intrinsic E', non-bridging oxygen hole center (NBOHC) and peroxide group (POR). The displacement of the atomic nucleus means that it deviates from the original equilibrium position, leaving a vacancy (Schottky defect) on the lattice or forming a vacancy-interstitial atom (Frenkel defect).
[0006] During the preparation of preforms, due to the randomness of the materials that make up the optical fiber, some imperfect structures will be formed, such as oxygen vacancies, non-bridging oxygen ions, bond breakage or atomic displacement. When the optical fiber works under normal conditions, the absorption caused by this factor can usually be ignored. However, if the optical fiber is exposed or works in a radiation environment, when the radiation reaches a certain dose, color centers will be formed at the defects due to the capture of electrons or holes generated during the irradiation process, which enhances the absorption caused by the defects and means that the signal attenuation will become more serious. With the rapid development of optical fiber communication technology and optical fiber sensing technology, optical fibers have begun to be used in various irradiation environments. Many special industrial and military applications require optical fibers to have good radiation resistance. Therefore, understanding the origin of radiation-induced color centers in optical fibers and the characteristics of various color centers is of great significance for the development of radiation-resistant optical fibers.
[0007] Usually, in conventional optical fibers, the core is doped with germanium to increase the refractive index, and pure silica is used as the cladding to form the waveguide structure of the optical fiber. When GeO2 is doped in quartz optical fiber, Ge replaces Si in the [SiO4] tetrahedron, causing the tetrahedron to be distorted, generating stress in the optical fiber and eventually forming defects. Moreover, these impurity atoms have a strong electron affinity and are easy to capture the charge generated after irradiation to form "color centers". The color centers absorb light of a specific wavelength and cause increased loss, which makes it impossible for the optical fiber to transmit optical signals normally.
[0008] The common method currently adopted by the industry to improve the radiation resistance of optical fiber is: using high-purity silica as the core to avoid the radiation-resistant optical fiber to produce light absorption color centers under long-term low-dose rate and short-term high-dose rate radiation; adding a certain amount of fluorine element to silica to make a low-refractive index cladding to form the optical fiber's light-guiding interface. While ensuring the transmission performance of the optical fiber, the formation of radiation-induced defect color centers is avoided.
[0009] However, in the optical fiber with pure silica core and fluorine-doped inner cladding, due to the mismatch of high temperature viscosity between the core and cladding, under the action of drawing tension during the drawing process, a large stress will be generated at the interface between the core and cladding, thereby causing strain, causing geometric fluctuations of the core / cladding interface, and causing interface inhomogeneity. We know that the propagation of light waves in optical fiber is transmitted forward through interface reflection. Interface inhomogeneity will cause scattering loss. Interface inhomogeneity itself is also a defect of the optical fiber itself. Under irradiation environment, color centers will be generated, resulting in large radiation-induced losses. Summary of the invention
[0010] The main technical problem solved by the utility model is to provide a new type of radiation-resistant optical fiber, which eliminates or reduces the irregularity of the interface by matching the interface viscosity of the chlorine-doped core and the fluorine-doped cladding, thereby reducing the formation of "color centers", significantly reducing the radiation-induced loss of the optical fiber, and significantly improving its radiation resistance.
[0011] In order to solve the above technical problems, a technical solution adopted by the utility model is: to provide a new type of radiation-resistant optical fiber, including a chlorine-doped core, a fluorine-doped inner cladding and a pure SiO2 outer cladding arranged in sequence from the inside to the outside, the refractive index of the chlorine-doped core is greater than the refractive index of the pure SiO2 outer cladding, the refractive index of the pure SiO2 outer cladding is greater than the refractive index of the fluorine-doped inner cladding, the refractive index difference between the chlorine-doped core and pure SiO2 and the refractive index difference between the fluorine-doped cladding and pure SiO2 form the main guiding light plane of the optical fiber fundamental mode, the fluorine-doped inner cladding is formed by doping silica with fluorine to reduce the refractive index to form a waveguide structure, the chlorine-doped core and the fluorine-doped inner cladding are matched at the interface viscosity to eliminate or reduce the irregularity of the interface and thus reduce radiation-induced loss.
[0012] In a preferred embodiment of the present invention, the inner and outer coatings of the radiation-resistant optical fiber are copolymers of one or more radiation-proof functional monomers and acrylate.
[0013] In a preferred embodiment of the present invention, the radiation protection functional monomer is samarium methacrylate, lead methacrylate or gadolinium methacrylate, and the mass fraction of the radiation protection functional monomer in the coating is 3wt.%-6wt.%.
[0014] In a preferred embodiment of the present invention, the relative refractive index difference between the core and the silica is , the core viscosity is , the relative refractive index difference between the fluorine-doped inner cladding and silica is , the viscosity of the fluorine-doped inner cladding is , the viscosity matching can be calculated according to the following formula: ; , when viscosity matches, the following conditions must be met: , and finally get the following formula: , , is the core / cladding refractive index difference.
[0015] In a preferred embodiment of the present invention, when the chlorine and fluorine materials are doped, at 1650°C, according to different doping concentrations by weight, the viscosity of the quartz glass can be obtained by referring to the following formula: , is the viscosity of pure silica; , T is Kelvin degree; fluorine and chlorine doping, , .
[0016] In order to solve the above technical problems, another technical solution adopted by the utility model is: to provide a method for preparing the above-mentioned new type of radiation-resistant optical fiber, comprising the following steps: a. using the VAD method to make a fiber core: purified air is introduced into the reaction container, and a discharge pump in the exhaust pipe on one side of the reaction container ensures that the internal pressure is stable. A pure SiO2 burner head is used to deposit a pure SiO2 fiber core, and the deposition surface is always maintained at a position between the SiO2 core rod burner heads. The porous mother material of the prepared SiO2 core is sintered and dehydrated, and the core rod loose body is doped with chlorine with SiCl4 in a sintering furnace. The quartz loose body can be diffused and doped with chlorine into the quartz glass in a high-temperature furnace. Before and / or before the loose body is converted into a closed pore state, the loose body is doped with chlorine to become a completely sintered glass body, and a dry gas composed of helium and chlorine is passed through, and the helium penetrates into the porous glass particles. The gas remaining in the preform rod during the hydrolysis reaction is removed, and the chlorine gas is used for dehydration to replace the OH in the porous body, so that the basic absorption peak of the generated Si-Cl bond is at a wavelength of 25μm, thereby keeping it away from the working wavelength of the quartz optical fiber of 0.8-2μm. The residual water in the preform rod is removed, and after dehydration treatment, the OH content in the quartz glass can be reduced to about 1ppb; b. Use the POVD process to complete the fluorine-doped inner cladding and the pure SiO2 outer cladding: SiF4 and SiF6 undergo MFC and source chemical gases SiCl4 and O2 to produce chemical vapor phase reactions in plasma O2 and N2 to generate pure SiO2 or fluorine-doped SiO2 deposits. Under the high temperature energy of the plasma, a glass body is directly formed. After the deposition is completed, the target rod is divided to obtain the required tubular outer cladding glass body; c. Wire drawing: The above-mentioned glass preform rod is inserted into a wire drawing furnace for high-temperature wire drawing at 2200℃. The optical fiber is drawn into an optical fiber, and optical fiber coating is required in the optical fiber drawing process. The coating diameter is 242±5µm. The coating is divided into an inner layer and an outer layer. The inner and outer coatings are copolymers of one or more radiation protection functional monomers and acrylates. The mass fraction of the radiation protection functional monomers in the coating is 3wt.%-6wt.%.
[0017] In a preferred embodiment of the utility model, in step a, the tail pipe is clamped by a fixture to pass purified air into a reaction vessel in a clean space, and the pure SiO2 core porous matrix is deposited by a pure SiO2 core upper burner and a pure SiO2 core lower burner using an oxidative hydrolysis method to generate oxides. The rotation and lifting speed of the pure SiO2 core porous matrix are controlled by PID control so that the bottom deposition surface is always maintained at a position between the pure SiO22 core upper burner and the pure SiO2 core lower burner; the pressure inside the entire reaction vessel is controlled by a pressure sensor and transmitted to the control system, and then the pneumatic valve and the exhaust pump are adjusted by PID control to discharge the waste gas generated by the manufacturing process, while ensuring the stability of the pressure and airflow inside the reaction vessel. Similarly, the camera and the pyrometer collect information and transmit it to the monitor and the deposition body profile. The display is controlled by a PID control system, with an ejection mass of 38 g / min, a flame temperature of 1780°C, exhaust gas discharged by a discharge pump, an internal pressure of the reaction vessel of 5 pa, and a surface temperature of the porous matrix of the deposited pure SiO2 core of 1080°C. The rotation speed is maintained at 20 r / min, and the position deviation should be 50 μm. The prepared porous matrix of the pure SiO2 core is sintered and dehydrated, and the porous matrix of the pure SiO2 core is doped with chlorine using SiCl4 in a chlorine-doped sintering furnace. The porous matrix of the pure SiO2 core is doped with chlorine before and / or when the porous matrix of the pure SiO2 core is converted into a closed pore state, and is completely sintered and formed into a chlorine-doped core glass body in the presence of SiCl4 at a temperature above 1300°C.
[0018] In a preferred embodiment of the utility model, in the step b, the chlorine-doped fiber core glass body is fixed on a lathe chuck, the chlorine-doped fiber core glass body is driven to rotate by the lathe chuck, the plasma torch is fixed on a carriage, and the carriage moves the plasma torch along the length direction of the chlorine-doped fiber core glass body, so that the material is deposited on the chlorine-doped fiber core glass body to form the required tubular outer cladding glass body, the plasma gas delivery pipe and the source chemical gas are delivered to the plasma torch, the high-frequency generator provides a high-frequency electric field with a frequency of 5.28±0.13MHz and a power of 60KW through a coil to excite the plasma, and the source chemical substance generates a chemical in the plasma. The deposit of pure SiO2 or fluorine-doped SiO2 generated by gas phase reaction directly forms a glass body under the high temperature energy of plasma. The plasma gas is firstly dried by a plasma gas dryer to remove moisture to ensure that its hydroxyl content is less than 2ppm. The carrier gas O2 of the reaction gas is firstly dried by a dryer to remove moisture to ensure that its hydroxyl content is less than 0.5ppm, and then the source gas SiCl4 is taken out by a bubbler and transported to the plasma torch. The formation of the fluorine-doped sunken cladding is achieved by controlling the SiF4 and SiF6 flow rates at MFC27 to control the F doping amount. After the deposition is completed, the required fluorine-doped inner cladding and pure SiO2 outer cladding can be obtained.
[0019] In a preferred embodiment of the utility model, in the step c, the glass preform rod is inserted into a drawing furnace for high-temperature drawing at 2200°C to draw into an optical fiber, and the drawing tension is set to 30-45g. The optical fiber drawing process requires optical fiber coating, and the coating diameter is 242±5µm. The coating is divided into an inner and outer layer, and the inner coating diameter is 180-190µm. The Young's modulus of the inner coating is 0.5-2MPa, and the Young's modulus of the outer coating should be greater than 600MP.
[0020] In a preferred embodiment of the present invention, the doping concentration of chlorine in step a is 1 wt %.
[0021] The beneficial effects of the utility model are as follows: the novel radiation-resistant optical fiber of the utility model has interface viscosity matching between the silica chlorine-doped fiber core and the silica fluorine-doped inner cladding, so that the radiation-induced loss of the optical fiber can be significantly reduced and the radiation resistance performance thereof is significantly improved.
[0022] The novel radiation-resistant optical fiber of the utility model absorbs or blocks high-energy rays through the internal and external radiation-resistant coatings of the optical fiber, further alleviating the influence of radiation on the performance of the optical fiber, thereby improving the radiation resistance of the optical fiber. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present utility model, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present utility model. For those skilled in the art, other drawings can be obtained based on these drawings without creative work, among which:
[0024] Figure 1 It is a cross-sectional diagram of the viscosity-matching optical fiber refractive index distribution of the novel radiation-resistant optical fiber of the utility model;
[0025] Figure 2 This is a schematic diagram of the effect of germanium, fluorine, and chlorine doping on the refractive index of quartz;
[0026] Figure 3 This is a schematic diagram of making a chlorine-doped fiber core using the VAD method;
[0027] Figure 4 This is a schematic diagram of chlorine-doped sintering of the fiber core;
[0028] Figure 5 It is a schematic diagram of manufacturing fluorine-doped inner cladding and pure SiO2 outer cladding by POVD method;
[0029] Figure 6 This is a schematic diagram of the structure of a new type of radiation-resistant optical fiber; 1 / 0, chlorine-doped core, 102, fluorine-doped inner cladding, 103, pure SiO2 outer cladding. DETAILED DESCRIPTION
[0030] The technical scheme in the embodiment of the utility model will be described clearly and completely below. The structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification, so that people familiar with this technology can understand and read them, and are not used to limit the limiting conditions that can be implemented in the utility model, so they have no substantial technical significance. Any modification of the structure, change of the proportional relationship or adjustment of the size, without affecting the effect that can be produced by the utility model and the purpose that can be achieved, should still fall within the scope that the technical content disclosed in the utility model can cover. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and so on quoted in this specification are only for the convenience of narration, and are not used to limit the scope that can be implemented. The change or adjustment of the relative relationship, without substantial change of the technical content, should also be regarded as the scope that can be implemented in the utility model.
[0031] See also Figure 1 A novel radiation-resistant optical fiber includes a chlorine-doped core 101, a fluorine-doped inner cladding 102 and a pure SiO2 outer cladding 103 arranged in sequence from the inside to the outside. The refractive index of the chlorine-doped core is greater than that of the pure SiO2 outer cladding, and the refractive index of the pure SiO2 outer cladding is greater than that of the fluorine-doped inner cladding. The difference in refractive index between the chlorine-doped core and pure SiO2 and the difference in refractive index between the fluorine-doped cladding and pure SiO2 form the dominant light plane of the optical fiber fundamental mode. The fluorine-doped inner cladding forms a waveguide structure by reducing the refractive index of silica doped with fluorine. The chlorine-doped core and the fluorine-doped inner cladding match the interface viscosity to eliminate or reduce the irregularity of the interface, thereby reducing the radiation-induced loss. The optical fiber with a chlorine-doped core and a fluorine-doped inner cladding can eliminate or reduce the irregularity of the interface by matching the interface viscosity between the core and the cladding, thereby reducing the formation of "color centers" and reducing the radiation-induced loss, thereby improving the radiation resistance of the optical fiber. The core / cladding interface viscosity is different, and the stress generated by the interface strain during drawing causes the interface deformation to become the source of radiation-induced loss. Therefore, the interface viscosity matching is to reduce the loss when the optical fiber works in an irradiated environment.
[0032] Design of Viscosity-matched Fiber with Chlorine-doped Core and Fluorine-doped Cladding:
[0033] For the viscosity matching problem, assume that the relative refractive index difference between the core and silica is , the core viscosity is , the relative refractive index difference between the fluorine-doped inner cladding and silica is , the viscosity of the fluorine-doped inner cladding is , the viscosity matching can be calculated according to the following formula:
[0034] set up: ; ,
[0035] When viscosity is matched, the following conditions must be met:
[0036] ,
[0037] Finally, the following formula is obtained: , , is the core / cladding refractive index difference.
[0038] When doping with chlorine or fluorine materials, at 1650°C, according to different doping concentrations (wt%), the viscosity of quartz glass can be found in the following formula:
[0039] , is the viscosity of pure silica;
[0040] , T is the kelvin degree;
[0041] When fluorine and chlorine doping is performed,
[0042] ,
[0043] .
[0044] According to the calculation setting The values can be obtained separately , The doping concentration of chlorine and fluorine can be obtained from this. Specific fiber parameters, such as core diameter and refractive index difference of each section, can be obtained by simulation method. The cut-off wavelength of the optical cable is set to 1530nm.
[0045] Figure 1 is an example refractive index profile of a viscosity-matched optical fiber. is the refractive index difference between the chlorine-doped fiber core and pure silica, The refractive index difference between the fluorine-doped shallow depressed cladding and pure silica forms the dominant light plane of the optical fiber fundamental mode.
[0046] Effect of doping on the refractive index of quartz
[0047] The molar percentage of germanium, fluorine and chlorine doped in quartz glass and its effect on the refractive index of quartz at the same temperature can be considered to be linearly related. The specific effect can be seen Figure 2 .
[0048] As a multivalent metal atom, the form of germanium doping in quartz glass is generally consistent with the form of silicon atoms in the silicon dioxide lattice. The doping of germanium atoms in the lattice is characterized by replacing the original position of silicon atoms, replacing the [O=Si=O] structure with the [O=Ge=O] structure. Therefore, from a macroscopic point of view, it can be considered that the GeO2 molecule replaces the position of SiO2.
[0049] The doping form of halogen atoms is different from that of germanium atoms. After entering quartz, halogen atoms will not replace the position of silicon atoms, but will combine with silicon atoms by using the dangling bonds of silicon in the glass or opening the silicon-oxygen bonds, that is, forming the form of Si-X.
[0050] Comparison of the refractive index change caused by halogen atom doping: When the dopant is chlorine, it interrupts the ≡Si-O-Si≡ bond of quartz glass and replaces it with a ≡Si-Cl bond, resulting in the rearrangement of the quartz glass network structure. The radius of the chlorine ion is larger than that of the oxygen ion (the radius of the chlorine ion is 181pm, and the radius of the oxygen ion is 140pm), and the volume occupied is larger, which plays a role in expanding the network structure in the quartz glass, resulting in a significant decrease in the tightness of the structure, thereby reducing the viscosity of the glass and thus reducing its melting temperature. On the other hand, the final structure of the quartz glass whose structure is interrupted by chlorine is more open, and the ion polarizability increases, thereby increasing the refractive index of the quartz glass. The radius of the fluorine ion is 133pm, which is slightly different from the radius of the oxygen ion, and has less effect on the structure. Compared with chlorine, fluorine has a smaller polarizability, and the binding energy of the Si-F bond is much greater than the binding energy of the Si-O bond, so the overall polarizability of the quartz glass is reduced. Although fluorine changes the structure of the quartz glass, it causes a decrease in the ion polarizability, thereby reducing the refractive index of the quartz glass.
[0051] In addition, since the relative atomic masses of germanium, fluorine and chlorine are different, when calculating the mass percentage, the conversion between mass percentage and molar percentage can be seen in the following formula:
[0052]
[0053] Among them, Mr(A) is the relative atomic mass of the doping element, Mr(B) is the relative molecular mass of pure quartz, and Mr(C) is the molecular mass of the smallest lattice of the corresponding doping element in quartz glass (i.e., germanium is [GeO2], fluorine is [SiO 1.5 F], chlorine is [SiO 1.5 Cl]).
[0054] Since the molecular weight of the dopant relative to the overall quartz is relatively small, it can be approximately assumed that there is also a linear relationship between the mass percentage and the refractive index of the doped quartz.
[0055] Effect of doping on quartz loss
[0056] The Rayleigh scattering loss is the sum of the Rayleigh scattering loss caused by density fluctuation and the Rayleigh scattering loss caused by component fluctuation. The Rayleigh scattering loss caused by density fluctuation is shown in the following formula:
[0057]
[0058] Where λ is the wavelength of incident light, p is the photoelastic coefficient, n is the refractive index, and k is B is the Boltzmann constant, β T is the isothermal compressibility, T f The fictive temperature of optical fiber is defined as the temperature at which the SiO2 liquid structure solidifies and transforms into a glassy state.
[0059] Since Rayleigh scattering is mainly caused by freezing of density fluctuations, it is proportional to the fictive temperature. Therefore, reducing the fictive temperature can reduce the Rayleigh scattering coefficient. When chlorine is doped into silica glass, the viscosity of the glass can be reduced, thereby reducing its fictive temperature. Therefore, chlorine-doped silica glass has a smaller Rayleigh scattering loss caused by density fluctuations.
[0060] Furthermore, adding dopants that reduce the viscosity of the glass to the core layer can reduce the structural relaxation time of the glass during fiber drawing, which is beneficial to improving the uniformity of density, thereby reducing the Rayleigh loss caused by density fluctuations. Chlorine is more beneficial to reducing Rayleigh scattering than fluorine. Chlorine hardly causes concentration fluctuations, but it can reduce the relaxation time of drawing annealing and reduce the fictive temperature, so chlorine doping is beneficial to reducing fiber loss.
[0061] The increase in dopant concentration will cause an increase in Rayleigh scattering loss due to composition fluctuations. The Rayleigh scattering loss due to composition fluctuations is shown in the following formula:
[0062]
[0063] Where M j and x j are the relative molecular mass and doping amount of the minimum lattice formed by doping the jth dopant in the silicon dioxide lattice; N A is Avogadro's constant; the partial differentials of refractive index n and density ρ are determined by experimental data. The Rayleigh scattering loss caused by component fluctuations in the core is proportional to the molecular mass of the minimum lattice formed by doping and the doping amount (wt%). The molecular mass of germanium is 104.6, while the molecular mass of chlorine is 87.45; relative to SiO2, the refractive index is increased by 0.1%, and 1.8wt% of germanium is required, while chlorine only needs 1wt%, so the Rayleigh scattering loss caused by component fluctuations in the core due to chlorine doping is much smaller than that of germanium doping. The greater the Rayleigh scattering loss caused by density fluctuations and component fluctuations caused by doping, the greater the lattice defects caused by it, and the greater the loss (radiation-induced loss) caused by the color center formed when it works in a radiation environment. Vice versa. Therefore, the radiation-induced loss of the interface viscosity matching optical fiber of the chlorine-doped core and the fluorine-doped inner cladding can be significantly reduced, and its radiation resistance can be significantly improved.
[0064] The manufacturing method of the novel radiation-resistant single-mode optical fiber comprises the following steps:
[0065] (1) Using VAD method to make chlorine-doped fiber core:
[0066] The porous matrix of pure SiO2 fiber core is prepared by VAD method: the deposition surface is always kept at the position between the SiO2 core rod torch heads; purified air is introduced into the reaction vessel, and the exhaust pump in the exhaust pipe on one side of the reaction vessel ensures the stability of its internal pressure; the pure SiO2 torch head is used to deposit the pure SiO2 fiber core; the porous matrix of the prepared SiO2 fiber core is sintered and dehydrated, and the core rod loose body is chlorine-doped with SiCl4 in the sintering furnace. The structure of quartz glass is very loose, and certain gas ions are allowed to diffuse through the network at high temperature, so that chlorine can be diffused and doped into the quartz glass in the high-temperature furnace in the quartz loose body deposited by the VAD process. That is, the loose body is chlorine-doped before and / or at this time when it is converted into a closed pore state, and at a temperature higher than 1300°C, in the presence of SiCl4, it becomes a completely sintered glass body.
[0067] During this process, dry gas consisting of helium and chlorine is passed. The role of helium is to penetrate into the porous glass particles to remove the gas remaining in the preform during the hydrolysis reaction. Since helium is the substance with the smallest atomic volume except hydrogen, and it is also an inert gas, it is the best choice for this function. Chlorine is used for dehydration to remove the residual water in the preform. The essence of chlorine dehydration is to replace the OH in the porous body, so that the basic absorption peak of the generated Si-Cl bond is at a wavelength of 25μm, thereby keeping it away from the working wavelength of quartz optical fiber 0.8-2μm. After dehydration, the OH content in quartz glass can be reduced to about 1ppb to ensure the low loss performance of the optical fiber.
[0068] The VAD process can be used to produce a chlorine-doped fiber core refractive index profile distribution, and SiCl4 or Cl2 can be used as the source precursor of the dopant. Chlorine is originally its product when VAD prepares preform rods. The basic reaction equation is that silicon tetrachloride and oxygen react to produce silicon dioxide and chlorine:
[0069] SiCl4+O2→SiO2+2Cl2
[0070] However, there will still be some residual chlorine doping in the prepared quartz glass. The reason is that the reaction equation can be regarded as the redox reaction of oxygen oxidizing silicon tetrachloride, which is the process in which oxygen atoms gradually replace the chlorine atoms around silicon tetrachloride. If the oxygen content is insufficient, incomplete oxidation will occur. The product that can be stably present in incomplete oxidation is SiClO 1.5 , the oxygen content can be reduced by increasing the partial pressure ratio of silicon tetrachloride in the raw material gas or increasing the partial pressure ratio of chlorine gas, thereby forming a situation similar to incomplete oxidation and obtaining quartz glass with a higher chlorine doping concentration.
[0071] Therefore, both silicon tetrachloride and chlorine can be regarded as dopants, among which silicon tetrachloride is both a dopant and a raw material, and chlorine is both a product and a dopant.
[0072] Using VAD method to make SiO2 chlorine-doped fiber core: (such as Figure 3 , as shown in 4)
[0073] The entire manufacturing process uses a fixture 1 to clamp the tail pipe in a clean space reaction container 9 to pass purified air 2 to achieve a Class 100 clean space effect, uses an oxidative hydrolysis method to generate oxides, uses a pure SiO2 core upper blowtorch 10 and a pure SiO2 core lower blowtorch 11 to deposit a pure SiO2 core porous matrix 8, and uses a PID control 16 to control the rotation and lifting speed of the pure SiO2 core porous matrix 8, so that the bottom deposition surface 12 is always maintained at a position between the pure SiO2 core upper blowtorch 10 and the pure SiO2 core lower blowtorch 11; the pressure inside the entire reaction container 9 is controlled by a pressure sensor 3 and transmitted to a control system 13, and then passed through The pneumatic valve 4 and the exhaust pump 5 are adjusted by the PID control 16 to discharge the waste gas generated during the manufacturing process, and at the same time, the pressure and airflow inside the reaction container 9 are kept stable. The camera 6 and the pyrometer 7 collect information and transmit it to the monitor 15 and the deposited body profile display 14, and then the control system 13 is controlled by the PID control 16. The ejection mass is 38g / min, the flame temperature is 1780℃, the exhaust pump 5 discharges the waste gas, the pressure inside the reaction container 9 is 5pa, and the surface temperature of the porous matrix 8 of the pure SiO2 core after deposition is 1080℃. The rotation speed is maintained at 20r / min, and the position deviation should be 50μm. The porous matrix 8 of the pure SiO2 core is sintered and dehydrated, and the porous matrix 8 of the pure SiO2 core is chlorine-doped with SiCl4 in the chlorine-doped sintering furnace 17, that is, the porous matrix 8 of the pure SiO2 core is chlorine-doped before and / or at this time. And at a temperature higher than 1300°C, in the presence of SiCl4, it is completely sintered and formed into a chlorine-doped core glass body 8a.
[0074] (2) Use POVD process to complete the fluorine-doped inner cladding and pure SiO2 outer cladding
[0075] SiF4, SiF6 undergoes chemical vapor phase reaction in plasma O2, N2 with source chemical gas SiCl4, O2 to generate pure SiO2 or fluorine-doped SiO2 deposits, which directly form glass under the high temperature energy of plasma. After the deposition is completed, the target rods are divided to obtain the required tubular outer cladding glass.
[0076] The radiation-resistant optical fiber cladding is formed by doping silicon dioxide with fluorine to reduce the refractive index to form a waveguide structure. Fluoride raw materials doped with fluorine include CCl2F2, C2F2, SiF4, SF6, CF4, etc. If CCl2F2 (Freon) is used as the raw material, the following reaction formula is obtained in the chemical vapor phase reaction:
[0077] 3CCl2F2+2SiCl4+3O2= 2SiO1.5F+7Cl2↑+3CO↑ +2F2↑
[0078] From the above reaction formula, it can be seen that fluorine exists in the molecular lattice array of silicon dioxide in the form of Si-F bonds in quartz glass. However, the following equilibrium reaction will also occur with this reaction formula:
[0079] 4SiO 1.5 F↔SiF4↑+SiO2
[0080] This also means that during the fluorine doping process, fluorine is unstable inside quartz and is easily lost or diffused under high temperature. At the same time, this also shows that SiF4 should be the best fluorine doping agent.
[0081] POVD process to produce fluorine-doped inner cladding and pure SiO2 outer cladding: (such as Figure 5 shown)
[0082] The chlorine-doped core glass body 8a is fixed on a lathe chuck 18, and the chlorine-doped core glass body 8a is driven to rotate by the lathe chuck 18. A plasma torch 19 is fixed on a carriage 20, and the carriage 20 moves the plasma torch 19 along the length direction of the chlorine-doped core glass body 8a, causing the material to be deposited on the chlorine-doped core glass body 8a to form the desired tubular outer cladding glass body 21. The plasma gas (O2, N2) delivery pipe 22 and the source chemical gas (SiCl4, O2) delivery 23 are delivered to the plasma torch 19, and a high-frequency generator provides a high-frequency electric field with a frequency of 5.28+ / -0.13MHz and a power of 60KW through a coil (not shown) to excite the plasma, and the source chemical substance produces a chemical vapor reaction in the plasma to generate a deposit of pure SiO2 or fluorine-doped SiO2, which directly forms a glass body under the high temperature energy of the plasma. The plasma gas is firstly passed through the plasma gas dryer 24 to remove moisture, ensuring that its hydroxyl content is less than 2ppm; the carrier gas (O2) of the reaction gas is firstly passed through the dryer 25 to remove moisture, ensuring that its hydroxyl content is less than 0.5ppm, and then the source gas (SiCl4) is taken out through the bubbler 26 and transported to the plasma torch 19. The formation of the fluorine-doped sunken cladding is to control the F doping amount by controlling the flow of SiF4 and SiF6 at MFC27. After the deposition is completed, the desired fluorine-doped inner cladding and pure SiO2 outer cladding can be obtained.
[0083] (3) Wire drawing
[0084] The glass preform is inserted into a drawing furnace for high-temperature drawing at 2200°C to form an optical fiber. The drawing tension is set to 30-45g. The optical fiber formed by these processing parameters is less susceptible to drawing-induced stress, which is detrimental to the optical transmission properties of the optical fiber (including waveguide propagation performance). Fiber coating is required in the optical fiber drawing process, and the coating diameter is 242±5µm. The coating is divided into two layers, inner and outer. The inner coating diameter is 180-190µm. The inner coating needs to use a coating with a low Young's modulus to improve the optical fiber's anti-microbending performance. The Young's modulus of the inner coating is 0.5-2MPa, and the outer coating uses a coating with a higher Young's modulus to increase the mechanical and environmental protection properties of the optical fiber. The Young's modulus of the outer coating should be greater than 600MPa.
[0085] The radiation-resistant coating of the optical fiber absorbs or blocks high-energy rays, further alleviating the impact of radiation on the performance of the optical fiber, thereby improving the radiation resistance of the optical fiber. The radiation-resistant coating of the optical fiber is a UV-cured acrylic resin, and the inner and outer coatings are copolymers of one or more radiation-proof functional monomers and acrylates; the radiation-proof functional monomer is any one of samarium methacrylate, lead methacrylate, and gadolinium methacrylate. The mass fraction of the radiation-proof functional monomer in the coating is 3wt.%-6wt.%.
[0086] Different from the prior art, the design and production technology of the viscosity-matched radiation-resistant optical fiber of the utility model is applicable to single-mode optical fiber, multi-mode optical fiber and various non-standard optical fibers with large numerical apertures. By matching the interface viscosity of the chlorine-doped core and the fluorine-doped cladding, the irregularity of the interface is eliminated or reduced, thereby reducing the formation of "color centers", so that the radiation-induced loss of the optical fiber can be significantly reduced, and its radiation resistance performance can be significantly improved.
[0087] The above schematically describes the present invention and its implementation methods, which are not restrictive. The drawings show only one implementation method of the present invention, and the actual structure is not limited thereto. Therefore, if ordinary technicians in this field are inspired by it and design structural methods and embodiments similar to the technical solution without creativity without departing from the purpose of the present invention, they should all fall within the protection scope of the present invention.
Claims
1. A novel radiation-resistant optical fiber, characterized in that: The invention comprises a chlorine-doped core, a fluorine-doped inner cladding and a pure SiO2 outer cladding which are arranged in sequence from the inside to the outside. The refractive index of the chlorine-doped core is greater than that of the pure SiO2 outer cladding, the refractive index of the pure SiO2 outer cladding is greater than that of the fluorine-doped inner cladding, the refractive index difference between the chlorine-doped core and pure SiO2 and the refractive index difference between the fluorine-doped cladding and pure SiO2 form the dominant light plane of the optical fiber fundamental mode, the fluorine-doped inner cladding forms a waveguide structure by lowering the refractive index by doping silicon dioxide with fluorine, and the interface viscosity of the chlorine-doped core and the fluorine-doped inner cladding is matched to eliminate or reduce the irregularity of the interface, thereby reducing radiation-induced loss.
2. The novel radiation-resistant optical fiber according to claim 1, characterized in that: The relative refractive index difference between the core and silica is , the core viscosity is , the relative refractive index difference between the fluorine-doped inner cladding and silica is , the viscosity of the fluorine-doped inner cladding is , the viscosity matching can be calculated according to the following formula: ; , when viscosity matches, the following conditions must be met: , and finally get the following formula: , , is the core / cladding refractive index difference.
Citation Information
Cited By
Radiation-resistant large-core-diameter energy transmission optical fiber and preparation method thereof
CN121348493A
